2022
DOI: 10.3390/nu14234956
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Membrane Docosahexaenoic Acid (DHA) and Lipid Profile in Preterm Infants at Birth and Over the First Month of Life: A Comparative Study with Infants at Term

Abstract: An observational comparative study was designed to assess the fatty acids profile in erythrocyte membrane phospholipids of 30 preterm neonates (<32 weeks gestation) at birth and after 1 month of life versus a convenience sample of 10 infants born at term. The panel of fatty acids included the families and components of saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), and n-6 and n-3 polyunsaturated fatty acids (PUFAs) as well as enzyme activity indexes and fatty acids ratios. At birth, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…One of the most important findings of the present study was the correlation between donors' DHA intake and DHA plasma levels and the DHA content of the raw DHM. This result is important because, in a recent study [91], the DHA levels in DHM were lower than in the mother's own milk for very preterm infants, indicating that DHM provides an insufficient supply of DHA to these patients, who comprise an already DHA-deficient population [92]. Our results are consistent with those of the only study that has determined the DHA content of DHM in relation to the DHA intake of milk donors.…”
Section: Discussionsupporting
confidence: 88%
“…One of the most important findings of the present study was the correlation between donors' DHA intake and DHA plasma levels and the DHA content of the raw DHM. This result is important because, in a recent study [91], the DHA levels in DHM were lower than in the mother's own milk for very preterm infants, indicating that DHM provides an insufficient supply of DHA to these patients, who comprise an already DHA-deficient population [92]. Our results are consistent with those of the only study that has determined the DHA content of DHM in relation to the DHA intake of milk donors.…”
Section: Discussionsupporting
confidence: 88%
“…The greatest changes occur in the first weeks after birth, and interestingly the relative levels of DHA and ARA also decrease when fish-oil contain lipids are administered [13 ▪ ,14]. Postnatal fatty acid trajectories differ significantly between relative or absolute units [13 ▪ ], but most studies have shown that preterm infants fed either breast milk or the common preterm formulas (containing 0.2–0.37% of total fatty acids as DHA) have blood levels of LC-PUFAs consistent with DHA deficiency [15].…”
Section: Estimates Of the Need For Long Chain-polyunsaturated Fatty A...mentioning
confidence: 99%